Socioeconomic Factors and Policy Improvements: A Case Study of Smash-and-grab Robbery in California - Gu, Hengming (Journal of Student Research, 2025)
Smash-and-grab robberies, characterized by groups of individuals breaking into stores, stealing goods, and quickly fleeing, have become a significant issue in California. This study examines the increase in these crimes and explores the underlying socioeconomic and legal factors contributing to their rise. In particular, it focuses on the impact of California’s Proposition 47, which reclassified certain offenses to reduce prison overcrowding but may have inadvertently led to an increase in property crimes. This paper also proposes a two-pronged approach to address smash-and-grab robberies: strengthening immediate law enforcement measures, such as foot patrols and technological integration, while addressing long-term social inequalities through improved education and financial support for marginalized communities. The findings emphasize the need for targeted law enforcement strategies and caution policymakers to carefully evaluate the effects of legal reforms like Proposition 47. Ultimately, proactive policies and robust enforcement can help reduce smash-and-grab incidents and create a safer business environment throughout California.